Corporate Social Responsibility, Earnings Management, and Family Ownership: A Comprehensive Literature Review - Anugrah, Miranda; Kusumaningtias , Rohmawati (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to provide some comprehensive insights into the relationship between Corporate Social Responsibility (CSR) and earnings management by highlighting the moderating role of family ownership. Using a literature review approach, 12 empirical studies published between 2017 and 2024 were analyzed to identify patterns and differences in the findings. The results indicate that most studies found a negative relationship between CSR and earnings management. However, several other studies found a positive relationship, where CSR is used as a legitimacy tool to mask earnings management practices. Family ownership has been shown to play a significant role in moderating this relationship.